Analisis Rasio Keuangan untuk Penilaian Kinerja pada Pemerintah Daerah Kabupaten Gunung Kidul - Rigel Nurul Fathah (EBBANK, 2017)
The objective of this research is to analyze the financial performance of Gunungkidul regency from 2010 until 2014 seen from : (1) Effectiveness Ratio PAD, (2) Regional Financial Efficiency Ratio, (3) Ratio of Suitability, (4), Ratio of Growth, and (5) Ratio of Independence Regional Finance. This research is quantitative descriptive. This research collecting secondary data at Central Bureau of Statistics (BPS) Yogyakarta. Data analysis techniques used quantitative descriptive formula : Effectiveness Ratio PAD, Regional Financial Efficiency Ratio, Ratio of Suitability, Ratio of Growth and Ratio of Regional Financial Independence. The analysis showed the financial performance of Regency Gunungkidul seen from (1) Ratio Effectiveness of PAD can be considered effective, because the average effectiveness by 131,8% (2) Efficiency Ratio Regional Financial classified as not efficient since the average magnitude of this ratio at 109,8%. (3) Ratio of Suitability can be said that the Gunungkidul regency allocated most of its budget for operating expenditure area which is an average of 71,26% compared with the average capital expenditure amounted to 9,92%. (4) Ratio of Growth Income, Revenue, Operating expenditure always increase from year to year and Growth Capital Expenditure is volatile (5) Ratio of Financial Independence area is still classified as Low once and in the category of relationship patterns Instructive because the average ratio of 10%.